2015
DOI: 10.1042/bst20150128
|View full text |Cite|
|
Sign up to set email alerts
|

Learning from each other: ABC transporter regulation by protein phosphorylation in plant and mammalian systems

Abstract: The ABC (ATP-binding cassette) transporter family in higher plants is highly expanded compared with those of mammalians. Moreover, some members of the plant ABCB subfamily display very high substrate specificity compared with their mammalian counterparts that are often associated with multidrug resistance (MDR) phenomena. In this review we highlight prominent functions of plant and mammalian ABC transporters and summarize our knowledge on their post-transcriptional regulation with a focus on protein phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 119 publications
(136 reference statements)
1
36
0
Order By: Relevance
“…Co-immunoprecipitation data revealed that blue light reduced ABCB19-TWD1 interaction, which is dependent on phot1 (Christie et al 2011). These data together support a model in which ABCB phosphorylation by AGC kinases, such as phot1 or PID, alters the chaperoning role of TWD1 on ABCB PM trafficking by reducing ABCB-TWD1 interaction (Aryal et al 2015). A similar mode of action has been suggested for CFTR/ABCC7 secretion that is dependent both on interaction with FKBP38 and phosphorylation of the regulatory R domain, the equivalent of the ABCB linker, by protein kinase A.…”
Section: Abcb Transport Activity Is Regulated By Agc Protein Kinasessupporting
confidence: 68%
See 4 more Smart Citations
“…Co-immunoprecipitation data revealed that blue light reduced ABCB19-TWD1 interaction, which is dependent on phot1 (Christie et al 2011). These data together support a model in which ABCB phosphorylation by AGC kinases, such as phot1 or PID, alters the chaperoning role of TWD1 on ABCB PM trafficking by reducing ABCB-TWD1 interaction (Aryal et al 2015). A similar mode of action has been suggested for CFTR/ABCC7 secretion that is dependent both on interaction with FKBP38 and phosphorylation of the regulatory R domain, the equivalent of the ABCB linker, by protein kinase A.…”
Section: Abcb Transport Activity Is Regulated By Agc Protein Kinasessupporting
confidence: 68%
“…Two recent studies support the concept that members of the plant-specific AGC protein kinase family, orthologs of mammalian protein kinases A, C and G, regulate ABCBs involved in auxin transport (Aryal et al 2015): first, the AGC4 kinase, PHOTROPIN1 (phot1) was shown to interact with the NBDs of ABCB19 (but not with ABCB1). Co-expression in HeLa cells reduced ABCB19 activity, which was further accelerated by blue light irradiation.…”
Section: Abcb Transport Activity Is Regulated By Agc Protein Kinasesmentioning
confidence: 91%
See 3 more Smart Citations